2015
DOI: 10.15406/jdvar.2015.02.00037
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Avian Infectious Coryza: It’s Re-Emerging Trends on Epidemiology, Etiologic Characterization, Diagnostics, Therapeutic and Prophylactic Advancements

Abstract: Avian Infectious coryza, a highly opportunistic respiratory tract infection caused by Avibacterium paragallinarum is now believed to be evolving as a re-emerging disease of poultry birds. Albeit adoption of strong precautionary/prophylactic measures i.e. vaccine/vaccination practice, the infection continues as complicated pattern of disease course worldwide that results in massive economic and production losses. India, being a major admirer of poultry products suffers tremendously with this insidious infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
8
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
5
8
1
3
Order By: Relevance
“…Gram staining was done on 24 isolates and showed Gramnegative coccobacilli. The results are similar to the findings of Patil et al [22] and Deshmukh et al [23]. Then, the isolates underwent biochemical tests, such as catalase, oxidase, urease, indole, motility, and carbohydrate fermentation tests.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Gram staining was done on 24 isolates and showed Gramnegative coccobacilli. The results are similar to the findings of Patil et al [22] and Deshmukh et al [23]. Then, the isolates underwent biochemical tests, such as catalase, oxidase, urease, indole, motility, and carbohydrate fermentation tests.…”
Section: Discussionsupporting
confidence: 88%
“…A. paragallinarum had the highest resistance level against E, followed by TE, S, DO, K, and W. Most of A. paragallinarum isolates have shown resistance primarily to sulfonamides and partly to aminoglycosides (especially S) and TE [23]. The resistance level against E was similar to other studies [9,15], whereas the high level of resistance against TE was similar to the study reported by Thenmozi and Malmarugan [29], and Heuvelink et al [30].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Poultry are susceptible to many infectious diseases such as infectious bursal disease, infectious bronchitis, infectious laryngotracheitis, Marek's disease, Newcastle disease, Fowl pox, avian influenza, fowl cholera, fowl typhoid, bacillary white diarrhea, chronic respiratory disease, and coccidiosis, etc. (Deshmukh et al, 2015;Jordan, 2017;García, 2017;Yuan et al, 2018;Alkie and Rautenschlein, 2016;Wua et al, 2011;Reddy et al, 2016). Morbidity and mortality caused by the pathogens are very high leading to negative impact on production and human welfare due to shortage of food supply.…”
Section: Poultry Vaccinesmentioning
confidence: 99%
“…Вакцинация птиц обеспечивает выработку напряженного иммунитета, обусловленного наличием антигемагглютинирующих антител. Выявлена тесная связь между протективной функцией иммунитета и титром специфических антител в реакции торможения гемагглютинации (7,11,12). Вакцинация позволяет значительно сократить использование антибактериальных препаратов, что, в свою очередь, способствует предотвращению проблем, связанных с появлением резистентности у микроорганизмов и остаточными количествами антибиотиков в продукции птицеводства (12)(13).…”
unclassified